Growing complexity of (expanded) carrier screening: Direct-to-consumer, physician-mediated, and clinic-based offers. (October 2017) - Chokoshvili, Davit; Vears, Danya F.; Borry, Pascal
Abstract : Since the introduction of out-of-hospital health-related genetic tests more than a decade ago, the landscape of genetic testing services has grown in complexity. Although initially most genetic tests for health purposes were offered as direct-to-consumer services, that is, without the mediation of a medical professional, currently many commercial providers require that their tests be ordered by a licensed physician. At the same time, some commercially developed health-related genetic tests are gaining support from the professional medical community and are finding their way into clinical practice. Therefore, we differentiated between three types of genetic testing offers: direct-to-consumer, physician-mediated, and clinic-based genetic testing. Expanded carrier screening tests for recessive disorders are currently available through all the three models of genetic testing. Herein, we review the present landscape of expanded carrier screening offers by highlighting the distinct issues associated with each of the three types of genetic testing. Highlights: Classification of genetic testing services into three categories is proposed. Current landscape of expanded carrier screening for recessive disorders is described. Issues with expanded carrier screening offers through the three models are discussed.